Sensitivity of post treatment positron emission tomography/computed tomography to detect inter-fractional range variations in scanned ion beam therapy - Handrack, Josefine; Tessonnier, Thomas; Chen, Wenjing; Liebl, Jakob; Debus, Jürgen; Bauer, Julia; Parodi, Katia (Acta oncologica, 2017)
Background: Ion therapy, especially with modern scanning beam delivery, offers very sharp dose gradients for highly conformal cancer treatment. However, it is very sensitive to uncertainties of tissue stopping properties as well as to anatomical changes and setup errors, making range verification highly desirable. To this end, positron emission tomography (PET) can be used to measure decay products of bþ-emitters created in interactions inside the patient. This work investigates the sensitivity of post treatment PET/CT (computed tomography) to detect inter-fractional range variations. Material and methods: Fourteen patients of different indication underwent PET/CT monitoring after selected treatment fractions with scanned proton or carbon ion beams. In addition to PET/CT measurements, PET and dose distributions were simulated on different co-registered CT data. Pairs of PET data were then analyzed in terms of longitudinal shifts along the beam path, as surrogate of inter-fractional range deviations. These findings were compared to changes of dose-volume-histogram indexes and corresponding dose as well as CT shifts to disentangle the origin of possible PET shifts. Results: Biological washout modeling (PET simulations) and low (<55 Bq/ml) activity concentrations (offline PET measurements, especially for 12C ions) were the main limitations for clinical treatment verification. For two selected cases, the benefit of improved washout modeling based on organ segmentation could be demonstrated. Overall, inter-fractional range shifts up to ±3 mm could be deduced from both PET measurements and simulations, and found well correlated (typically within 1.8 mm) to anatomical changes derived from CT scans, in agreement with dose data. Conclusions: Despite known limitations of post treatment PET/CT imaging, this work indicates its potential for assessing inter-fractional changes and points to future developments for improved PETbased treatment verification.
Gesehen am 12.07.2018